2020
DOI: 10.1111/epi.16518
|View full text |Cite
|
Sign up to set email alerts
|

Seizure‐related apneas have an inconsistent linkage to amygdala seizure spread

Abstract: Objective: Sudden unexpected death in epilepsy (SUDEP) is a frequent cause of death in epilepsy. Respiratory dysfunction is implicated as a critical factor in SUDEP pathophysiology. Human studies have shown that electrical stimulation of the amygdala resulted in apnea, indicating that the amygdala has a role in respiration control.Unilateral amygdala stimulation resulted in immediate onset of respiratory dysfunction occurring only during nose breathing. In small numbers of patients, some but not all spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Similarly, seizure spread to these regions may be driving ictal apneas ( Dlouhy et al, 2015 ; Nobis et al, 2019 ). The involvement of the extended amygdalar regions (CeA and BNST) in ictal apneas may explain why the amygdala at large does not always produce apneas when activated by seizures ( Park et al, 2020 ). The PBN has a known role in the modulation of breathing ( Dutschmann and Herbert, 2006 ; Navarrete-Opazo et al, 2020 ) and has been targeted to rescue respiratory dysfunction in developmental disorders ( Abdala et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, seizure spread to these regions may be driving ictal apneas ( Dlouhy et al, 2015 ; Nobis et al, 2019 ). The involvement of the extended amygdalar regions (CeA and BNST) in ictal apneas may explain why the amygdala at large does not always produce apneas when activated by seizures ( Park et al, 2020 ). The PBN has a known role in the modulation of breathing ( Dutschmann and Herbert, 2006 ; Navarrete-Opazo et al, 2020 ) and has been targeted to rescue respiratory dysfunction in developmental disorders ( Abdala et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…These brain areas include the amygdala (32, 36, 64), the hippocampus head and body, anterior parahippocampal gyrus, and antero-mesial fusiform gyrus (65, 66). A pediatric study found apneas and seizure spread to the amygdala were strongly correlated (67), an adult study failed to replicate this (64). Electrical stimulation to the insula and left cingulate gyrus decreased cardiac output and induced cardiac asystole in epilepsy patients without effects on breathing (68,69).…”
Section: Brain Areas Linked To Autonomic Controlmentioning
confidence: 99%
“…For example, stimulation of the basolateral, basomedial, and central regions consistently resulted in apnea, whereas stimulation of the more lateral amygdala failed to affect breathing (Rhone et al, 2020 ). Therefore, not all amygdala seizures result in apnea (Park et al, 2020 ). It is also worth mentioning that amygdala stimulation elicited apnea even during sleep (Nobis et al, 2018 ) when SUDEP occurs most frequently (Nobili et al, 2011 ).…”
Section: Descending Seizure Propagation Through Synaptic Connectivitymentioning
confidence: 99%